A note on the generalised Lomax distribution as a lifetime model - Ong, S H; Ong, E.K. (Malaysian Journal of Science, 1999)
The behaviour of the hazard rate of the generalised Lomax distribution is examined. The hazard rate is either decreasing or upside-down bathtub shaped. An example of a goodness-of-fit to lifetime data is given.